3D Password Enabling Using Gait Technology - Charan, BalaSai; Rao, Venkat Narayana; Chandra, Saras (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
Existing authentication systems is suffering with many weaknesses. In general, textual passwords are used to secure normal user accounts or data. However, these can be cracked by some techniques such as, if the number of characters is being fixed and there will be a finite number of possibilities as the length of the password is fixed (maximum allowed length). The current existing graphical password system uses less space than that of the textual passwords space. Firstly considering a 3D password, it is a combination of more than one authentication systems.. When the user intend to set a 3D password, it redirects into a 3D-virtual environment where in different types of objects navigates. User password will be set in the order in which he/ she selects/ interacts with those objects. Password key will be set based on intended 3D virtual environment and on the objects selected. Combining many systems of certification is an advantage of this 3D technique, providing higher security than the existing arrangement. Human gaits can also be combined with 3D password to provide more security to the users. Textual passwords may be easily ruptured because of fixed maximum possible length and harmfull as there is a chance of losing token based techniques/smart cards such as passports. Graphical passwords can be easily recorded as they take much time. In this paper, the usage of Human gaits face expressions, walk style, smile, etc. are taken into consideration and captured ultimately to attain better secured authenticated system than exiting scenario.